2009
DOI: 10.1139/z09-018
|View full text |Cite
|
Sign up to set email alerts
|

Apparent survival, natal philopatry, and recruitment of Barrow’s goldeneyes (Bucephala islandica) in the Cariboo–Chilcotin region of British Columbia, Canada

Abstract: We used capture–resight data to evaluate apparent survival, natal philopatry, and recruitment of Barrow’s goldeneyes ( Bucephala islandica (Gmelin, 1789)) in British Columbia, Canada. Median ages of first pairing and first breeding for females were 2 years and 3 years, respectively. The Cormack–Jolly–Seber model that best fit our data indicated that apparent survival rates (Φ) differed according to sex, year, and age class at marking. Estimates were similar for after-hatch-year (AHY) females (0.62) and AHY mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 16 publications
4
13
1
Order By: Relevance
“…Therefore, to the extent that we underestimated φ A we must have overestimated φ J . Our average post‐fledging survival estimate (φ J’ ; x = .16 ± 0.05) is significantly lower than existing estimates for female Barrow's goldeneyes (0.68; Boyd et al ). However, we were unable to further adjust for potential sex differences in survival because detection probability for males was zero in our study.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Therefore, to the extent that we underestimated φ A we must have overestimated φ J . Our average post‐fledging survival estimate (φ J’ ; x = .16 ± 0.05) is significantly lower than existing estimates for female Barrow's goldeneyes (0.68; Boyd et al ). However, we were unable to further adjust for potential sex differences in survival because detection probability for males was zero in our study.…”
Section: Discussioncontrasting
confidence: 87%
“…The lower post‐fledging survival estimates we report may reflect potential differences in mortality or dispersal patterns compared to Boyd et al's (2009) study. Our study population is near the northern distributional limit of the goldeneye's breeding range (Eadie et al ), and may be subject to harsher wintering conditions, longer migration, and a more constrained nesting phenology, all of which may create different mortality patterns, relative to temperate latitude populations (Boyd et al ). Alternatively, nest sites may have been more limited in our study population compared to Boyd et al's (2009), leading to higher natal dispersal that lowered our estimates of post‐fledging survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative density‐dependent relationship between conspecific nest box occupancy during prospecting and subsequent recruitment could be explained through multiple demographic processes, including reduced second‐year survival, delaying recruitment, increased likelihood of engaging in alternative nesting strategies at recruitment, or natal dispersal. Adult survival, which is assumed to be similar to second‐year survival rates in sea ducks (Boyd et al , Schamber et al ), in our study population is relatively high (0.86 ± 0.11, Lawson et al ) and did not appear to be controlled by density‐dependent factors. The individual probability of recruitment for individuals that survived to two years of age is also very high (0.96 ± 0.06, Lawson et al ), and suggests that goldeneyes in our study population begin breeding as early as possible, rather than delaying recruitment.…”
Section: Discussionsupporting
confidence: 74%
“…Though natal philopatry and breeding site fidelity are assumed to be high in goldeneyes (Savard and Eadie , Pöysä et al ), a recent study of the closely related Barrow's goldeneye in British Columbia, Canada reported that only a small proportion of yearling females that returned to their natal grounds for nest prospecting were actually recruited into the breeding population (Boyd et al ). The authors detected a negative correlation between first‐year apparent survival and subsequent within‐cohort apparent survival, and suggested that within‐cohort density dependence may reduce local recruitment (Boyd et al ), though nest site availability was not examined. However, we evaluated the effect of first‐year survival on subsequent recruitment rates and population growth for cohorts but found no support for an effect of first‐year survival (models containing dphi t‐ 1 in Supplementary material Appendix A Table A1, A2).…”
Section: Discussionmentioning
confidence: 99%